Iatrogenic bradyarrhythmia: previous conduction disturbances predicted need for permanent pacing. (26th April 2021) - Esteves, AF; Parreira, L; Marinheiro, R; Fonseca, M; Farinha, JM; Pinheiro, A; Ferreira, J; Mesquita, D; Amador, P; Lopes, A; Fonseca, N; Caria, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: In bradyarrhythmia due to negative chronotropic medication, the need for permanent pacing after drug discontinuation is not always straightforward. Purpose: Evaluate prevalence and predictors of the need of permanent pacing in patients with symptomatic bradyarrhythmia under negative chronotropic drugs. Methods: We retrospectively studied patients admitted to the emergency room between January 2012 and December 2018 with symptomatic bradyarrhythmia who were under negative chronotropic drugs. We analysed patient demographic factors, previous medical history or electrocardiographic abnormalities and concomitant drugs. We evaluated the laboratory results, electrocardiographic and echocardiographic parameters at admission. During follow-up we analysed mortality, re-hospitalizations and device implantation. We used cox regression to assess the predictors of device implantation. Results: 85 patients, were admitted to the emergency room, 47% male, median age 81 (76-87) years. The majority of patients (39, 46%) were admitted with syncope/presyncope and presented with complete AV block (62 patients, 73%). 54% had previous bundle branch block and most (69%) were taking beta blockers. Of note, 17 (20%) presented with ionic disturbances. 17 (20%) patients needed temporary pacing and 60 (71%) patients needed permanent pacing, implanted during index-hospitalization in 78 (92%) patients. Intra-hospital mortality was 5%. During a median follow-up of 66 months, 31 (36%) patients were re-hospitalized and 7 (8%) needed device implantation. Global mortality was 26%. In univariate analysis, previous bundle branch block predicted the need for permanent pacing, while presence of atrial fibrillation, antipsychotic/antidepressant use, acute kidney failure and hypo/hyperkalaemia precluded its requirement. In multivariate analysis, previous bundle branch block was the only independent predictor of the need for permanent pacing. Conclusion: In this group of patients with iatrogenic symptomatic bradyarrhythmia, the need for permanent pacing was independently associated with the presence of previous conduction disturbances.